Pharmaceutically controlled designer circuit for the treatment of the metabolic syndrome - Ye, Haifeng; Charpin-El Hamri, Ghislaine; Zwicky, Katharina; Christen, Matthias; Folcher, Marc; Fussenegger, Martin (Proceedings of the National Academy of Sciences - PNAS, 2013)
Synthetic biology has significantly advanced the design of genetic devices that can reprogram cellular activities and provide novel treatment strategies for future gene- and cell-based therapies. However, many metabolic disorders are functionally linked while developing distinct diseases that are difficult to treat using a classic one-drug-one-disease intervention scheme. For example, hypertension, hyperglycemia, obesity, and dyslipidemia are interdependent pathologies that are collectively known as the metabolic syndrome, the prime epidemic of the 21st century. We have designed a unique therapeutic strategy in which the clinically licensed antihypertensive drug guanabenz (Wytensin) activates a synthetic signal cascade that stimulates the secretion of metabolically active peptides GLP-1 and leptin. Therefore, the signal transduction of a chimeric trace-amine-associated receptor 1 (cTAAR1) was functionally rewired via cAMP and cAMP-dependent phosphokinase A (PKA)-mediated activation of the cAMP-response element binding protein (CREB1) to transcription of synthetic promoters containing CREB1-specific cAMP response elements. Based on this designer signaling cascade, it was possible to use guanabenz to dose-dependently control expression of GLP-1-Fc(mIgG)-Leptin, a bifunctional therapeutic peptide hormone that combines the glucagon-like peptide 1 (GLP-1) and leptin via an IgG-Fc linker. In mice developing symptoms of the metabolic syndrome, this three-in-one treatment strategy was able to simultaneously attenuate hypertension and hyperglycemia as well as obesity and dyslipidemia. Using a clinically licensed drug to coordinate expression of therapeutic transgenes combines drug- and gene-based therapies for coordinated treatment of functionally related metabolic disorders.